(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
This article reviews the health conditions and risks associated with schoolchildren carrying heavy backpacks. We examine evidence from peer-reviewed studies on how excessive backpack weight and suboptimal backpack design affect children’s bodies. Key outcomes identified in the literature include back pain and other musculoskeletal symptoms, changes in posture and gait, and physiological stress responses to load carriage. We also review interventions and ergonomic recommendations to mitigate these risks.